An atypical presentation of ulcerative colitis: case report - Avanti Saoji; Madhura Kavishwar; Praveen Unki; Surbhi Rathi (Egyptian Pediatric Association Gazette, 2024)
Abstract Background Bloody diarrhea in children often indicates a severe gastrointestinal illness. Although infections are the most likely cause, inflammatory bowel disease (IBD) is a close mimic. IBD generally presents with chronic and persistent symptoms requiring long-term treatment. Hence, acute or atypical presentations may mislead the physician leading to delays in diagnosis. We report the case of an atypical presentation of ulcerative colitis. Case presentation We present the case of a 6-year-old girl with acute symptoms of bloody diarrhea, fever, abdominal pain, and tenesmus for 5 days. The child came to us after the non-resolution of symptoms after treatment from a local practitioner. The child was found to have signs of chronic malnutrition and clubbing on general examination. After ruling out infective causes, the child was evaluated further by colonoscopy, which revealed lesions suggestive of ulcerative colitis, and hence started on topical and oral treatment for the same. Conclusion Awareness about the disease and its atypical presentations like poor growth, anemia, or extraintestinal manifestations is necessary, especially in primary healthcare and resource-poor settings as it can lead to early diagnosis, referral, and treatment initiation.